The relationship of time-reversal and multi-channel decision feedback equalization in underwater acoustic communication. (13th June 2019) - Kida, Yukihiro; Shimura, Takuya; Deguchi, Mitsuyasu
Abstract: The relationship between the performance of the passive time-reversal (PTR) communication technique and multi-channel decision feedback equalization for moving-source single-input/multiple-output (SIMO) communication problems in the multipath-rich shallow sea environment is investigated. Both methods are applied to a synthetic dataset of an underwater acoustic moving-source model, generated by the normal mode method, to evaluate utilization of the wavefield energy as an adaptive diversity-combining method. The results show that PTR followed by decision feedback equalization (PTR-DFE) is the more robust technique in a moving-source environment with moderate source speed. In particular, PTR-DFE can utilize most of the energy in moderate-speed conditions. It is also discussed how the performance of each method can be limited in the moving-source SIMO problem. The results indicate that the performance of PTR-DFE can be limited by the convergence property and filter tap length limitations of the DFE in problems with rapidly moving sources.